Human VPS13A is associated with multiple organelles and influences mitochondrial morphology and lipid droplet motility - Yeshaw, Wondwossen M; van der Zwaag, Marianne; Pinto, Francesco; Lahaye, Liza L; Faber, Anita IE; Gómez-Sánchez, Rubén; Dolga, Amalia M; Poland, Conor; Monaco, Anthony P; van IJzendoorn, Sven CD; Grzeschik, Nicola A; Velayos-Baeza, Antonio; et al. (eLife, 2019)
The VPS13A gene is associated with the neurodegenerative disorder Chorea Acanthocytosis. It is unknown what the consequences are of impaired function of VPS13A at the subcellular level. We demonstrate that VPS13A is a peripheral membrane protein, associated with mitochondria, the endoplasmic reticulum and lipid droplets. VPS13A is localized at sites where the endoplasmic reticulum and mitochondria are in close contact. VPS13A interacts with the ER residing protein VAP-A via its FFAT domain. Interaction with mitochondria is mediated via its C-terminal domain. In VPS13A-depleted cells, ER-mitochondria contact sites are decreased, mitochondria are fragmented and mitophagy is decreased. VPS13A also localizes to lipid droplets and affects lipid droplet motility. In VPS13A-depleted mammalian cells lipid droplet numbers are increased. Our data, together with recently published data from others, indicate that VPS13A is required for establishing membrane contact sites between various organelles to enable lipid transfer required for mitochondria and lipid droplet related processes.